Properties of Municipal Solid Waste Incinerator Ash in Concrete (International Journal of Engineering and Computer Science, 2015)
The Municipal Solid Waste Incineration (MSWI) residues are a worldwide studied topic over the last decades. So that to utilize the municipal solid waste is the one of the possibilities is to use MSWI ashes in concrete production, as it is done the bottom ash features the most convenient composition in concrete, and it is available in highest amounts among the MSWI ashes. The bottom ash was used as partial replacement of cement in concrete strength has to find, if the prepared concrete will get sufficient durability or not. The behavior of concrete with the bottom ash is differed from the control material due to presence of sulfates and chlorides in bottom ash.